The burden of hepatitis C virus in the world, China, India, and the United States from 1990 to 2019 - Yang, Jia; Qi, Jin-Lei; Wang, Xiao-Xiao; Li, Xiao-He; Jin, Rui; Liu, Bai-Yi; Liu, Hui-Xin; Rao, Hui-Ying (Frontiers in Public Health, 2023)
Background: Hepatitis C virus leads to an enormous health burden varying by location. Investigating the changes in HCV burden between different countries could provide inferences in managing HCV infection. Hence, we aim to explore the temporal tendency of HCV burden in China, India, and the United States, compared with the global level. Methods: Detail data on the total burden of HCV were collected from the Global Burden of Disease (GBD) 2019 database Joinpoint regression models were used to calculate annual percent changes (APCs) and detect the optimal joinpoints. The temporal trend and association between the burden of HCV and the Socio-demographic Index (SDI) were described. The decomposition of changes was analyzed to identify the contribution of the main factors. Results: 6.2 million new HCV infections, 0.54 million HCV-related deaths, and 15.3 million DALYs were estimated in 2019 globally, with an increase of 25.4%, 59.1%, and 43.6% from 1990, mainly due to population growth and aging. China experienced a sharp drop in age-standardized rates in 2019 while the United States showed an upward trend with the biggest increment among the three countries. India exhibited a fluctuating tendency with the highest DALY in 2019. Incidence was increasing in all locations recently. Conclusion: HCV remains a global health concern despite tremendous progress being made as incidence and age-standardized incident rates increased worldwide in recent years. China progressed more rapidly than the global level whereas the burden in the United States was deteriorating, suggesting more targeted intervention being established to realize the 2030 elimination.